KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH MEMODERASI PENGARUH MOTIVASI INTERNAL DAN KEDISIPLINAN TERHADAP KINERJA GURU SEKELOMPOK KERJA KERJA MADRASAH ALIYAH (KKMA) MAN 02 PATI - Ulil Albab, 12.52.02.0008; Suhari, Yohanes (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study is an attempt to find out or to test the principle transformational leadership in moderating the effect of internal and discipline motivation toward the teacherâs performanceÂ ofÂ MAN 2 Pati work group. The sample was conducted by using proportional random sampling. The sample consisted of 229 people. The sum of the sample could be obtained by using Slovin formula n = N/ N.d2+1). This study used some technics in testing the data. It involved validationtest using factor analysis, reliability test byusing Alpha Cronbach.Â This study used significance test and moderated regression analysis, coefficient of determination and significance test to prove the true of hypothesis and moderation test. The result of this study showed that the influence of internal motivation variable toward teacherâs performance, the influence of discipline variable toward teacherâs performance, the influence of principal transformational leadership toward teacherâs performance was,Â principal transformational leadership variable strengthened in teacherâs performance and principal transformational leadership variable strengthened the influence of discipline toward the teacherâs performance. Key Words: Internal Motivation, Discipline, PrincipleÂ Transformational Leadership and The Teacherâs Performance.